Treatment of hypercoagulability of burns - Hazán, Enrique; Grolero de Cat, María L (Cirugía del Uruguay, 1973)
Complications, their causes and death rate, in two groups of burned patients, are analyzed. One group was treated with Calciparine, the other served as witness. -This treatment is based on former experimental work. -The treatment is simple and inocuous. -Finally, the conclusion is that the group subject to this treatment had a better evolution.